Validation of the name Vochysia moskovitsiana (Vochysiaceae), with corrected type citation - Chuquimaco, Isau Huamantupa (Phytotaxa, 2016)
The name Vochysia moskovitsiana Huamantupa (2012: 142) was not validly published due to errors in the citation of the holotype. In the type paragraph following the name citation, a single gathering but more than one specimen, E. Gudiño 1190 (QCNE, MO) was cited as the type. This is a defective citation according to the International Code for Nomenclature (ICN) Article 40.7 (McNeill et al. 2012) because a single specimen is not indicated as the holotype. Although a separate collection, Gudiño & Gualinga 1622 (MO), is cited in the caption to Figure 2 as the holotype, the same specimen also appears in the list of paratypes on page 147. Thus the citation of type is entirely ambiguous, and this work does not constitute valid publication.